Pengaruh Regulasi Emosi Terhadap Kecemasan Kompetisi dengan Dukungan Sosial sebagai Moderator pada Atlet Remaja: Penelitian - Wahidatul Fitri; Raras Sutatminingsih; Tarmidi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Competitive anxiety is a major psychological challenge for adolescent athletes that can hinder optimal performance on the court. This study aims to examine the effect of emotion regulation on competitive anxiety and the role of social support as a moderator variable in adolescent badminton athletes. This study used a quantitative approach with a cross-sectional design. The participants were 203 adolescent badminton athletes (aged 10-15 years) in Medan City selected using purposive sampling technique. Data collection instruments included the Sport Anxiety Scale (SAS adaptation), Indonesian Emotion Regulation Questionnaire for Sport (IERQ4S), and Multidimensional Scale of Perceived Social Support (MSPSS). Data analysis was performed using Moderated Regression Analysis (MRA). The results showed that emotion regulation had a significant negative effect on competitive anxiety (p < .001). Social support was proven to moderate the relationship significantly (p < .001), where the interaction between emotion regulation and social support was able to strengthen the reduction in competitive anxiety with the effective contribution of the model increasing from 53.7% to 75.8%. The conclusion of this study is that synergy between internal capabilities (emotion regulation) and external factors (social support) is highly effective in reducing competitive anxiety in adolescent athletes.